Spawning biology of a hill stream fish, Botia almorhae Day of Kumaun Himalaya, Uttarakhand - Joshi, S K; Pathani, S S (Indian Journal of Fisheries, 2011)
The Almora loach, Botia almorhae is a beautifully coloured hill stream fish which breeds once in a year. Spawning biology of B. almorhae from Kumaun Himalaya was studied. The breeding season extended from May to August in the River Suyal, Kumaun Himalaya and the fish preferred to spawn in small rivulets (Gadhera), where the water velocity is very slow. The fecundity ranged from 908-3616 (76-154 mm fish). The length-weight relationship was W= -6.728+2.216L. The correlation between fecundity and total length (F=178+21.34x) and body weight and fecundity (F=109.2+431.7x) was highly significant (r=0.986682 and 0.96793, respectively). The K-values ranged from 0.52 (76-80 mm length group) to 0.63 (146-150 mm length group) in males, while in female fish, this value ranged from 0.53 (76-80 mm length group) to 0.65 (146-150 mm length group).